2000
DOI: 10.1667/0033-7587(2000)154[0429:tabhic]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Apoptosis by Hydroxymethylacylfulvene in Combination with Gamma Radiation in Prostate Tumor Cells

Abstract: Hydroxymethylacylfulvene (HMAF) is a novel agent with alkylating activity and is a potent inducer of apoptosis that is currently undergoing Phase II clinical trials for prostate cancer. This study explored the pro-apoptosis and anti-proliferative potential of HMAF in combination with gamma radiation in human prostate tumor cell lines. Apoptosis was assessed based on the generation of fragmented DNA, a terminal transferase flow cytometry assay, and cell morphology. In each of the tumor cell lines examined, radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 22 publications
0
17
1
Order By: Relevance
“…Thus, IR treatment within a clinically relevant dose range would predominantly express antiproliferative effects rather than cell killing. The significance of the IR-induced antiproliferative effects has been often underestimated compared to cell death (4,(6)(7)(8)(9), but in the present study we showed that a decrease of proliferation is the most prominent effect of γ-IR on DU 145 cells.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…Thus, IR treatment within a clinically relevant dose range would predominantly express antiproliferative effects rather than cell killing. The significance of the IR-induced antiproliferative effects has been often underestimated compared to cell death (4,(6)(7)(8)(9), but in the present study we showed that a decrease of proliferation is the most prominent effect of γ-IR on DU 145 cells.…”
Section: Discussioncontrasting
confidence: 44%
“…Accordingly, induction of apoptotic cell death plays an important role (4)(5)(6). Radiation biology studies in rat prostate adenocarcinoma have shown that irradiation-induced apoptosis occurred at a higher rate in well-differentiated tumors compared to anaplastic ones (7). Thus, increased radiosensitivity, judged by apoptotic cell death as an end point, was observed for well-differentiated tumors (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for less responsive tumor cells (SF 2 (36). However, the uncertainty of SF 2 could be notable (37). Since the uncertainty of SF 2 could be indicative, its impact was studied for SF 2 ranging from 0.3 to 0.9.…”
Section: Contrast Between Hypofractionation and Standard Fractionationmentioning
confidence: 99%
“…As Irofulven causes a predominant pre-mitotic form of cell killing, and radiation post-mitotic cell death, it can be envisaged that both therapies empirically will combine to kill cancer cells in at least an additive fashion, as previously noted by this group in prostate cancer cells. 10 Further studies will be required to determine whether Irofulven is a radiosensitizer in multiple other tumor cell types.…”
Section: Resurgence For Alkylating Therapy In Cancer?mentioning
confidence: 99%